Unpacking the political legitimacy of parliament in an emerging democracy: the case of Malawi, 1994 to 2011 - Jana, Michael Patrick Eliezer (My University, 2014)
Political legitimacy manifests differently in different state institutions, and comprehending its dynamics is a prerequisite to understanding power, authority, capacity, consolidation, and sustainability of any political regime. Supported by evidence from a case study of the Malawian parliament from 1994 to 2011, my original contribution to knowledge is that political legitimacy of representative institutions in emerging democracies has three minimum dimensions, namely: public perception of the acceptability and fairness of formal procedures guiding a representative institution; public emotional attachment to the institution; and public perception of performance effectiveness of the institution. I label these dimensions as juridical; symbolic; and instrumental legitimacy respectively. I therefore posit that, deficiency in any or some of the three legitimacy dimensions has the potential to compel those represented, who may be self-confessed democrats, to demand institutional reforms that ironically may go against the very tenets of multi-party democracy. The Malawi parliament case shows that legitimacy deficiency of parliament seems to be facilitated by public dissatisfaction with their local socioeconomic status, in the context of a dysfunctional local government, and coupled with the public perception of parliament as a responsible institution given its status in the perceived representation hierarchy that places it above the local government. This situation is aggravated given the fact that Malawi parliament, rightly so, is neither institutionally nor financially supported to directly address local development issues; and that, erroneously, the parliament is neither institutionally nor financially supported to effectively carry out its representation function despite representation carrying the status of a meta-function. The lack of political will for public consultations and lack of intra-party democracy in political parties represented in parliament has also tremendously eroded the influence of political parties hence further undermining the legitimacy of the whole multi-party regime. Using principles of external validity in case study research therefore, the Malawian case study provides analytical insights that can be extrapolated to understand political legitimacy of representative institutions in other emerging democracies that have similar context to that of Malawi.
Thesis submitted in fulfilment of the requirements for the Degree of Doctor of Philosophy in Political Science Graduate School for Humanities and Social Sciences University of the Witwatersrand
Keywords: Malawi|xPolitics and government|y1994-2011; Legislative bodies|zMalawi|xCommittees